Ten years of the Northeastern Nursing Network Journal — Rev Rene: a dream come true - Inácia Sátiro Xavier de França; Francisco Stélio de Sousa; Rafaella Queiroga Souto; Alexsandro Silva Coura; Andressa Kaline Ferreira Araújo; Lorita Marlena Freitag Pagliuca (Rev Rene)
The aim was to analyze the historical memory of the Rene Journal along a decade of its existence, highlighting its organization,scientific production and the achievements with regard to its indexing in databases. Phenomenological study whose data werecollected through a form submitted to free associations and interpreted in accordance with “The poetics of space”. The nuclei were:Federal University of Ceará (FUC) — The home of Rev Rene; the Rev Rene-nest — an open space for researchers in Health andrelated areas; Poetics of the drawers, safe and cupboards — the scientific capital of the journal at the readers’ disposal; The RevRene-shell — a poetic homology; The Rev Rene is round — Goals and actions for projection on the national and international scene.The Rev Rene transposed the dimension of the dream and has consolidated itself as a locus of science.